Predictors of career indecision among Iranian undergraduate students - Nasab, Mojgan Fadaei (2012)
Career indecision has been known as one of the major concerns of counselors and psychologists particularly among college and undergraduate students. Undecided students may have feelings of anxiety, uncertainty, fear, and confusion of their current majors and future career direction. This concern has led to numerous research related to career indecision and development of various counseling interventions and programs to help this group of students make effective career choices. Career indecision is a multidimensional issue which is linked to wide variety of factors. Several studies have reported the significant relationship between career indecision and career decision making self efficacy, anxiety, and parental attachment worldwide (e.g. Betz, 2004; Mau, 2000; Krumboltz, 1992; Guerra & Braungart-Reiker, 1999; Wolfe & Betz,2004). This correlation study was designed to determine the relationship between career indecision and career decision making self efficacy, state anxiety, trait anxiety, and attachment to mother and father. This study was carried out in two stages. In the first stage cluster sampling was used to select randomly 3 out of 10 public universities of Khozestan State south west of Iran, to examine the psychometric properties of the Career Decision Scale (CDS) and determine the prevalence of career indecision among Iranian undergraduate students. The respondents for this stage were 1610 freshmen and sophomores of three universities from Khozestan State. The aim of the second stage was to examine the relationship between career indecision and independent variables of the study with the moderating role of gender. In the second stage stratified random sampling was used and 158 undecided students were randomly selected based on their equal percentage of gender subgroups. Results revealed the CDS (Persian version) is a reliable instrument for Iranian undergraduate students with Alpha value of .805. Moreover, results of factor analysis indicated a two factorial structure of the scale with 4 components in each. Findings of present study showed almost 85% of students had career indecision with significantly higher career indecision among males (t = 2.758, p= .006) compared to females, and freshmen reported significantly higher career indecision than sophomores (t = 3.488, p < .001). A negative significant correlation was found between career indecision and career decision making self efficacy, and attachment to mother. On the other hand, a positive significant correlation was found between career indecision and state anxiety and trait anxiety. Further, the relationship between career indecision and attachment to father was not significant. However, regression analysis showed only career decision making self efficacy and trait anxiety significantly predicted career indecision of students. Together these factors accounted for 37% of the total variance of the career indecision among students. The result of Moderated Multiple Regression analysis showed that gender did not have a significant moderating effect in the relationship between career indecision and the predictor factors of the study. Based on the results of present study, it is recommended that university counseling services should consider the role of career decision making self efficacy and anxiety on students’ career indecision when assisting them. Mere reliance on traditional career guidance activities such as career information gathering and job search activities is not effective in helping undecided students. A combination of career counseling and psychotherapy would be effective in decreasing anxiety level and enhancing career decision making self efficacy of undecided students. However more esearch is needed to identify types of career indecision and proper counseling interventions to assist undecided students in Iran.